2018
DOI: 10.1021/acs.jafc.8b02940
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Fructooligosaccharides and Xylooligosaccharides as Substrates To Counteract the Undesirable Effects of Several Antibiotics on Elder Fecal Microbiota: A First in Vitro Approach

Abstract: Fructooligosaccharides (FOS) and xylooligosaccharides (XOS) were employed as substrates for in vitro fermentations to assess their capacity to counteract the effects caused by three antibiotics (ABs) at different doses on the elderly gut microbiota and its metabolic activity. The AB type and dose scarcely affected the total bacterial numbers and the microbiota composition after 24 h. However, in the presence of ABs, the relative percentages of Lactobacillus decreased (from 11.4% to 3.2% in the presence of XOS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 54 publications
6
23
0
1
Order By: Relevance
“…The next step in the present study was to investigate whether dietary fiber preparations could potentially counteract the effects of amoxicillin on the microbiota. The effect of amoxicillin along with doxycycline and clindamycin on the gut microbiota as well as the potency of FOS and two types of XOS to minimize their negative effect has been investigated using in vitro static batch fermentation model similar to that we established [15]. The authors also found that amoxicillin affected the microbiota in fiber dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step in the present study was to investigate whether dietary fiber preparations could potentially counteract the effects of amoxicillin on the microbiota. The effect of amoxicillin along with doxycycline and clindamycin on the gut microbiota as well as the potency of FOS and two types of XOS to minimize their negative effect has been investigated using in vitro static batch fermentation model similar to that we established [15]. The authors also found that amoxicillin affected the microbiota in fiber dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Propionate has been shown to inhibit cholesterol synthesis and butyrate, additionally to serving as a fuel for colon epithelial cells, and has been proposed to play an important role as a protective agent against chronic intestinal inflammation [12,13,14]. In addition to the beneficial metabolites from dietary fibers, prebiotic fibers could potentially reduce the negative effect of antibiotics on the gut microbiota by supporting the growth of the beneficial bacterial groups, and consequently, alleviating the symptoms the patients experience during the antibiotic therapy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…RS2 has been shown to alter the abundance of at least some intestinal bacterial genera and species, including enrichment of Ruminococcus bromii , Bifidobacterium adolescentis , Faecalibacterium prausnitzii , and E. rectale and reductions in Oscillospira , Lachnospiraceae , and Blautia [ 163 ]. FOS are found in natural fruits and vegetables and can promote the growth of beneficial gut microbiota such as Bifidobacterium and Lactobacillus [ 164 , 165 ]. FOS are effective in maintaining the diversity and stability of the microbial community, alleviating neuronal apoptosis and the swelling of brain tissues, regulating the synthesis and secretion of neurotransmitters, and downregulating the expression of tau and Aβ1-42 in the brain of rats with AD-like symptoms [ 166 ].…”
Section: Potential Therapeutic Strategies For Ad Targeting the Microbmentioning
confidence: 99%
“…Furthermore, the consumption of XOS results in increased indigenous Bifidobacterium sp. levels in elderly gut microbiota (Miguez et al 2018).…”
Section: Cellulosementioning
confidence: 99%